"Palinología del Paleogeno tardío-Neo geno temprano, pozo Aries x-l, Plataforma Continental Argentina, Tierra del Fuego" (Ameghiniana, 2014)
"ineteen cutting samples from the Aries x-I well, drilled in the Argentinecontinental shelf, offshore Tierra del Fuego, were analized for palynology. Marine and terrestrial palynomorphassemblages, fairly well preserved, though neither diverse nor abundant, were recoveredthroughout the studied interval, comprising depths between 240-640 m. Four sections, D, e, B and A frombotton to top are informally proposed on the basis of the palynological content. Sections D through B areconsidered Oligocene in age, most probably Upper Oligocene, whereas section A yielded Early Mioceneassemblages, according to previously recorded species distribution in nearby areas. Two marine eventswere recognized in sections e and A respectively. The first is characterized by the presence of highamounts of protoperidinioid dinoflagellate cysts (up to 98%) mostly Brigantedinium sp., and the second,by equivalent amounts of both major dinocyst groups-gonyaulacoids, protoperidiniods- with absolutedominance of Nematosphaeropsis rigida Wrenn (32 % of the assemblage). An environmental trend from estuarine-transitional restricted (section C) to neritic nearshore marine (section A) is suggested. Terrestrialpalynomorphs are abundant in sections e and A. Levels 500-550 m have large amounts of Nothofagiditesspp., pterydophyte spores and fungal rernains, probably reflecting forest vegetation in the surroundingarea. The interva1260-300 m, section A, yielded a diverse pollen grain assemblage mostly composed of theherbaceous and shrubby families Cyperaceae, Asteraceae, Chenopodiaceae and Anacardiaceae."